Health-related quality of life in patients with advanced well-differentiated pancreatic and extrapancreatic neuroendocrine tumors treated with surufatinib versus placebo: Results from two randomized, double-blind, phase III trials (SANET-p and SANET-ep). (July 2022) - Li, Jiarui; Cheng, Yuejuan; Bai, Chunmei; Xu, Jianming; Shen, Lin; Li, Jie; Zhou, Zhiwei; Li, Zhiping; Chi, Yihebali; Yu, Xianjun; Li, Enxiao; Xu, Nong; et al.
Abstract: Aim: To investigate the health-related quality of life (HRQoL) of patients who had neuroendocrine tumors (NETs) from SANET trials. Methods: Eligible patients were randomized in a 2:1 ratio to receive surufatinib or placebo. HRQoL questionnaires, including the European Organization for Research and Treatment of Cancer QLQ-C30 and QLQ-G.I.NET21, were collected. The prespecified HRQoL outcome was the mean change of scores from baseline to the last available visit for each domain. Time until definitive deterioration (TUDD) was defined as the time from randomization to deterioration of ≥10 points from baseline in domain score, disease progression, or death. Results: 370 patients were enrolled and randomly assigned to surufatinib (n = 242) or placebo (n = 128). No significant difference in mean scores change from baseline to the last available visit was observed for QLQ-C30 and QLQ- G.I.NET21 domains, with the exception of diarrhea. The mean score of diarrhea increased 11.7 points from baseline in the surufatinib arm and decreased 1.2 points in the placebo arm, and the between-group difference was 12.9 points. Compared with placebo, surufatinib treated patients had a significantly longer TUDD for dyspnea (hazard ratio [HR] 0.58; 95% confidence interval [CI], 0.39–0.86; P = 0.0058) and a significantly shorter TUDD for diarrhea (HR 2.91; 95% CI, 1.66–5.10; P < 0.0001). There were no significant differences in TUDD for the remaining domains of QLQ-C30 and G.I.NET-21. Conclusions: HRQoL was similar in patients treated with surufatinib and placebo except for diarrhea. The preservation of HRQoL supports surufatinib as a treatment option for NETs. Clinical trial information: ClinicalTrials.gov: NCT02589821, NCT02588170 . Highlights: Surufatinib showed a comparable effect on HRQoL to placebo for patients with NETs. Surufatinib increased risk of deterioration in diarrhea versus placebo. Surufatinib decreased risk of deterioration in dyspnea versus placebo. Surufatinib is a promising treatment option for advanced NETs.